STILL LIFE GENRE FROM THE OVERVIEW OF HISTORICAL DEVELOPMENT AND CURRENT TRENDS IN ART PHOTOGRAPHY - Скляренко, В. О.; ХИНЕВИЧ, Р. В. (Art and Design, 2025)
Purpose: to determine the features of the compositional construction of a photo still life as a means of artistic expression. Analyze the formative, light, color, and dynamic aspects of still life creation. Comparative and systematic analysis of compositional techniques in constructing expressive means: still life in the historical context of past and present masters based on the provided samples. A comparative and systematic analysis of the compositional solutions of both pictorial and photographic still life’s in terms of expressiveness and emotional perception in historical development and modern trends is carried out. Practical recommendations for using Creative modes in digital cameras and smartphones when shooting still life are given. Compositional solutions of various types of still life are analyzed in terms of historical development and the latest trends in this genre. The influence and connection of three-dimensional compositions, lighting, rhythm, and color schemes on the emotional perception of the work are highlighted. The author's illustrative material of different stylistic directions of still life is studied and presented. The obtained results can be used in the educational process in the preparation of bachelor's and masters of multimedia design.